Connection between hypoallergenic food and dyslipidemia in dogs: A nutritional myth? - Andressa Rodrigues Amaral; Thiago Henrique Annibale Vendramini; Natália Manuela Cardoso de Oliveira; Laís Oyama Cotrim Lima; Pedro Henrique Marchi; Marcio Antonio Brunetto; Júlio Cesar de Carvalho Balieiro (PLoS ONE, 2025)
The limited education in nutrition contributes to the spread of the “nutritionism” phenomenon, with unfounded concerns about certain diets, such as commercial hypoallergenic ones, and their supposed relationship with the development of dyslipidemia. This study aimed to evaluate the perception of veterinarians on the subject and test its veracity. For this, serum triglyceride and cholesterol data from 35 dogs were analyzed before and after consumption of a commercial hypoallergenic diet for 60 days. In addition, a survey was carried out with veterinarians to assess their beliefs about this diet. Finally, the fat content of commercial maintenance, light and other prescription diets were compared to that of 10 commercial hypoallergenic dog diets. The results showed that most veterinarians believed that hypoallergenic diets could cause dyslipidemia and has too much fat. The analysis showed that hypoallergenic diets have fat content in the range of maintenance diets and majority of prescription diets. Fat content of hypoallergenic diets was only higher than light diets and supporting diets for diabetes available in Brazil. Laboratory analysis identified no dogs with dyslipidemia development during the study. Therefore, hypoallergenic diets do not have a high fat content, but new studies should verify if, when used for prolonged periods, hypoallergenic would lead to dyslipidemia in healthy dogs or dogs with underlying diseases, as well as possible changes in the lipoprotein profile.